Capacity assessment of older t-beam bridges by nonlinear proxy finite-element analysis. (February 2020) - Schanck, Andrew P.; Davids, William G.
Highlights: Old reinforced concrete T-beam bridges are live-load tested. A novel, simplified finite element modeling technique is developed. Bridge rating factors are significantly improved. Models accurately predict bridge load distribution and girder ductility. Abstract: Older, cast-in-place, reinforced concrete T-beam bridges often have inadequate flexural rating factors, despite carrying modern traffic without distress. Three T-beam bridges were field tested under high bending moment and their strain response was recorded. The results allowed two of these bridges' HL-93 flexural rating factors to be increased to above 1.0, suggesting their ability to carry larger loads than predicted. A novel, nonlinear proxy finite element analysis (PFEA) technique was developed which enables the computationally efficient prediction of bridge response up to failure while accounting for girder ductility and load redistribution in the three-dimensional structure. PFEA uses a genetic algorithm to optimize constitutive and geometric parameters assigned to a shell element discretization of each girder that possesses moment-curvature response equivalent to that of the solid reinforced concrete T-beam sections. The resulting elastic and elastic-plastic shell element discretization is straightforward to implement in a three-dimensional model of a complete bridge using commercial finite element software. Using PFEA, the three field-tested bridges were analyzed and load rated, with resulting ratings consistently greater than those calculated by AASHTO and consistent with or greater than those inferred from field testing. The PFEA technique accurately predicts the real bridges' longitudinal and transverse load responses, and incorporates both girder ductility and load redistribution while also being able to assess bridges with non-uniform geometry.